Representações sociais de estudantes negros: universidade e trabalho - Santos, Elisabete Figueroa dos (2011)
Social indicators regarding education and employment relations in Brazil indicate that the inequalities are even more critical when the analysis is done from the ethnic-racial perspective, showing a situation of obvious disadvantage for the black population. However, the literature has shown that education is traditionally one of the main tools to promote social and economic rise of blacks. Thus, various higher education institutions have implemented the system of quotas, what results of the demands of the Brazilian black movement. Therefore, this research sought to understand the relationship between blackness, education and work, from the perspective of Black college students. The objective was to study the social representations that have UFSCar`s Black students on entering the public university system through reserve places, the course and chosen profession, and the inclusion and / or stay in the labor market. Specifically, we sought to analyze the Affirmative Action Program (AAP) of UFSCar, its proposals, policies and strategies; knowing the the socio-economic students features, especially those related to school life and work; the social representations of students about their training and entering the labor market; and finally, discuss the impact of the relations established in the university context on the ethnic-racial students. Individual interviews were conducted with 13 black students, who entered at UFSCar from 2008, through the system of quotas or not. In addition, group interviews were done with the students individually interviewed. It was possible to examine the relationships between the sense of belonging, ethnic-racial identity and representations that are engendered on race relations and affirmative action. We realize, therefore, Black students who identify themselves and claim themselves as Black, participants of assertive groups, engaged in racial discussions, and also identify themselves as reservists entering the vacancies for Black students. And there are those for whom race and ethnicity are not salient elements in their identity, do not share affirmative groups, and experience difficulties to assume themselves as freshmen at the reservation of seats for blacks. The representations about the implementation of quotas for Blacks are taken as something positive, because of the belief that they allow the entry of Blacks in the university; allow the entrance of the disadvantaged people; and reduce inequality. The seizure of this policy as a negative due to the representation of that institute such measures: assume the inability of Blacks; brings constitutional complications; shifts the focus from the real problem is education based, breeds prejudice, creates inequality, and finally, regard to the difficulty of defining who is Black in Brazil. The same relationships and forms of representations were found regarding the quotas for blacks in the labor market. We realized that those students who have an affirmed ethnic-racial identity represented the relations between being Black, higher education and the labor market in a more critical and proactive way. Thus, students whose ethnic-racial identity is not presented in a manner so prominent, represented these relationships in order to deny the existence of racism and in order to minimize the very affectation in a context of racial discrimination, which is pegged to the contrariety of affirmative action in about higher education and in the labor market.